MicroRNAs in Ewing Sarcoma - Dylla, Layne; Moore, Colin; Jedlicka, Paul (Frontiers in Oncology, 2013)
MicroRNAs (miRs) have emerged recently as important regulators of gene expression in the cell. Frequently dysregulated in cancer, miRs have shed new light on molecular mechanisms of oncogenesis, and have generated substantial interest as biomarkers, and novel therapeutic agents and targets. Recently, a number of studies have examined miR biology in Ewing sarcoma. Findings indicate that alterations in miR expression in Ewing Sarcoma are widespread, involve both EWS/Ets oncogenic fusion-dependent and independent mechanisms, and contribute to malignant phenotypes. miRs with prognostic potential have been identified, and several preclinical studies suggest that miR manipulation could be therapeutically useful in this aggressive disease. These and future studies of miR biology stand to expand our understanding of Ewing sarcoma pathogenesis, and may identify new biomarkers and treatment options.